Analisis Kevalidan dan Kepraktisan Media Beskuba Berbasis Budaya Pati untuk Pembelajaran Kalimat Siswa Kelas II : Penelitian - Sri Rahayu Kusumaningsih; Sabrina Putri Syahada; Rani Setiawaty (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Learning sentence structure in second-grade elementary classrooms often faces challenges due to the limited availability of relevant and contextual instructional media, which impacts students’ motivation and ability to identify subjects and predicates. This study aims to evaluate the practicality of the innovative learning media BESKUBA Budaya Pati as a solution to bridge the national curriculum with students’ local cultural context. Unlike previous studies that predominantly focus on learning outcomes or general vocabulary acquisition, this research emphasizes an analysis of the practicality aspects of implementing specific contextual media in authentic school settings. The research employed a descriptive-evaluative method within a Research and Development (R&D) framework using a mixed-methods approach. Data were collected through teacher practicality questionnaires, student responses, classroom observations, and interviews conducted at SD 3 Prambatan Lor. The main findings indicate that the BESKUBA media is highly practical, with an average media expert validation score of 89.48%, categorized as very feasible. Teachers reported that the media facilitated material delivery and improved time efficiency due to its locally familiar content, while students demonstrated increased independent learning activities and learning enthusiasm through a play-based approach. The primary conclusion of this study is that BESKUBA Budaya Pati serves as a practical and effective instructional tool for concretizing sentence structure learning through students’ local cultural identity. These findings imply the importance of developing learning media based on local wisdom to support the effective implementation of the Kurikulum Merdeka at the elementary school level.